2012
DOI: 10.1590/s1519-70772012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes das despesas com serviços de auditoria e consultoria prestados pelo auditor independente no Brasil

Abstract: The aim of the present study is to identify the factors affecting the auditing and consulting expenditures in Brazilian public companies. The current study was motivated by the lack of studies on auditing and consulting expenses in Brazil, whereas this matter has been researched for years in other countries. Data on Brazil are scarce because the disclosure of spending on auditing and consulting services provided by independent auditors only became mandatory in 2009. The disclosure of these data enables the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0
28

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 36 publications
(47 reference statements)
6
9
0
28
Order By: Relevance
“…These results reinforce the explanatory power of this variable and corroborate previous research (Simunic, 1980;Palmrose, 1986;Brinn et al, 1994;Joshi & AL-Bastaki, 2000;Köhler & Ratzinger-Sakel, 2012;Hallak & Silva, 2012, Hassan & Naser, 2013Kwon et al, 2014).…”
Section: Results Of Regressionssupporting
confidence: 91%
See 2 more Smart Citations
“…These results reinforce the explanatory power of this variable and corroborate previous research (Simunic, 1980;Palmrose, 1986;Brinn et al, 1994;Joshi & AL-Bastaki, 2000;Köhler & Ratzinger-Sakel, 2012;Hallak & Silva, 2012, Hassan & Naser, 2013Kwon et al, 2014).…”
Section: Results Of Regressionssupporting
confidence: 91%
“…Bortolon, Sarlo and Santos (2013) observed a negative relationship between corporate governance and auditing costs, suggesting that better governance practices have reduced the external audit risks, leading to lower charges. Hallak and Silva (2012) found that companies with better corporate governance levels spend more on audit.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…O tamanho da empresa pode ser um fator de interferência na precificação dos honorários, já que grandes companhias possuem operações mais complexas, que exigem maior esforço e mais horas do profissional de auditoria (Simunic, 1980;Francis, 1984;Hallak & Silva, 2012;Castro, Peleias & Silva, 2015; Borges, Nardi & Silva, 2017).…”
Section: Outros Determinantes Dos Honorários De Auditoriaunclassified
“…Essas empresas possuem mais recursos para o desenvolvimento do trabalho de auditoria, maior nível de especialização, maior competência e melhor reputação no trabalho de auditoria, por isso, cobram honorários mais caros por essa diferenciação na prestação de serviço (Francis, 1984;Yatim, Kent & Clarkson, 2006;Hallak & Silva, 2012;Castro et al, 2015; Borges et al, 2017).…”
Section: Outros Determinantes Dos Honorários De Auditoriaunclassified